Marketing activities, market orientation and other market variables influence on smes performance - Correia, Ricardo Jorge (2013)
This paper includes results on marketing, market orientation degree and environmental variables, such as competitive intensity and market turbulence, that can influence economic and financial performance of micro and small companies. The results indicate that: (a) marketing is seen by these companies as secondary, deserving minor practical actions that can be considered strategic, (b) at market orientation level, the market information affects positively performance indicators, (c) and economical and financial performance is superior in conditions of highly market turbulence and there is a negative relationship between competitive intensity and the companies ratio turnover/total assets.